Influência da adição do bagaço imobilizado na evolução dos compostos fenólicos durante o processo fermentativo de mosto de maçã - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The apple, one of the fruit more produced in the world, has been consumed in different ways, such as in raw fruits, juices, fermented products such as cider, distilled beverages, vinegar, as well as jams and dried fruits. The increase of the production scale of juices and ciders leads to increase of apple pomace production. This by-product characterizes as a fraction rich in fibers, sugars and phenolic compounds with antioxidant activity which are not totally extracted in the process. Therefore, the apple pomace shows potential to be used to improve the quality of foods and beverages. The aim of this work was to study the extraction of phenolic compounds from apple pomace immobilized during the fermentation of ciders. As well as, the evolution of this compounds during the fermentation and their impact on sensorial quality. It was used apples from Fuji variety to make 20 ciders, which were divided in 2 groups: cider I, control or without apple pomace addition, and cider II, with addition of apple pomace immobilized. The ciders fermentation were stopped, in supplicate, in the 1st, 4th, 7th, 11th and 15th days of fermentation, obtaining 2 fractions: the ciders and the fermented apple pomace, which were submitted to two consecutive extractions of methanol and acetone to phenolic composition analysis. It were carried out analysis od total nitrogen, color, pH, total titratable acidity, total phenolic composition, antioxidant activity, as well as individual phenolic composition, sugars, ethanol and sorbitol by HPLC. It was also carried out sensory analysis with 8 judges that knew the product, where it was evaluated the attributes of sourness, bitterness, astringency, color and odour quality by structured scales. It was observed a decrease of pH and an increase of titratable acidity of the ciders during fermentation. During the fermentation it was observed a reduction of 40% of total phenolic compounds of cider I, which can be relationed with the adsorption of compounds on cell wall of yeasts and the bioconversion of compounds. However, the cider II showed 93mg/L more total phenolic compounds than cider I, due the extraction of this compounds from apple pomace, and consequently, higher antioxidant activity. Flavonoids, especially flavonols (quercetin-3- rutinoside, quercetin-3-D-galactoside, quercetin-3-β-D-glucoside, quercetin-3-D-xyloside, quercetin-O-α-L-arabinofuranoside e quercetin-3-O-rhaminoside) was the main class of compounds extracted. Furthermore, occurred a extraction of sugars, in the beginning of fermentation of cider II, which impacted on their alcoholic degree which was higher on than cider I. It was observed a residual of fructose on ciders which was 0.3 g/L higher on cider II. The color of both ciders were yellow (h° near 90°), however, cider II showed higher lightness. Second the sensorial analysis results, the cider II ware more bitter and less sour, and their color was more light. The astringency for both beverages did not show significative difference (p > 0.05). the odour quality was evaluated by affective method, being the both ciders received notes between “ I liked quickly” and “I liked moderately”. In the residual apple pomaces, after fermentation, as expected had a reduction of the quantity of phenols an antioxidant activity. It was also observed an increase of total nitrogen, due the yeasts cell retention and also by extraction of sugars, which can concentrate other constituents. Therefore, the use of immobilized apple pomace on fermentation can improve the sensorial quality of ciders, reducing the perception of sourness, increasing the bitterness e improving the color of the beverage, without modify the perception of astringency, futhermor uncrease their phenolic composition and antioxidant activity.
Keywords: Sidra; Subproduto; Atividade antioxidante; CLAE; Cider; By-product; Antioxidant activity; HPLC; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS